Green Finance and Sustainability Practices in Encouraging Environmentally-Based Tourism Investment in Banyuwangi: Green Finance dan Praktik Keberlanjutan dalam Mendorong Investasi Pariwisata Berbasis Lingkungan di Banyuwangi - Yovita Vivianty Indriadewi Atmadjaja; mahfud; Susintowati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Green Finance faces challenges in balancing economic growth and environmental preservation. Limited funding, low public understanding, and waste and cultural management are the main obstacles in the development of sustainable tourism. The objective of this research is to analyze the role of Green Finance in the development of sustainable tourism in Banyuwangi, with a focus on the challenges, potential, and strategies to overcome existing obstacles. The research methodology uses a relevant Systematic Literature Review (SLR) approach. Researchers identify relevant literature based on inclusion and exclusion criteria. Data analysis organizes information, looking for patterns or themes. Synthesis of findings illustrates patterns and relationships among different findings. The comprehensive conclusion includes benefits, challenges, and policy recommendations. The results of the Green Finance research support the development of the sustainable tourism sector, maintaining the balance between economic growth and environmental preservation. Sustainable financing encourages environmentally friendly projects, transforms development paradigms, and supports nature conservation. The conclusion of Green Finance supports the development of sustainable tourism by integrating environmental preservation and economic growth. The recommendation of this research is that collaboration between the government, society, and the private sector is necessary to address funding challenges and create adaptive and coordinated policies.